Strength tests for elite rowers: low- or high-repetition? - Lawton, T. W.; Cronin, J. B.; McGuigan, M. R. (Journal of Sports Sciences, 2014)
The purpose of this project was to evaluate the utility of low- and high-repetition maximum (RM) strength tests used to assess rowers. Twenty elite heavyweight males (age 23.7 ± 4.0 years) performed four tests (5 RM, 30 RM, 60 RM and 120 RM) using leg press and seated arm pulling exercise on a dynamometer. Each test was repeated on two further occasions; 3 and 7 days from the initial trial. Per cent typical error (within-participant variation) and intraclass correlation coefficients (ICCs) were calculated using log-transformed repeated-measures data. High-repetition tests (30 RM, 60 RM and 120 RM), involving seated arm pulling exercise are not recommended to be included in an assessment battery, as they had unsatisfactory measurement precision (per cent typical error > 5% or ICC < 0.9). Conversely, low-repetition tests (5 RM) involving leg press and seated arm pulling exercises could be used to assess elite rowers (per cent typical error = 5% and ICC = 0.9); however, only 5 RM leg pressing met criteria (per cent typical error = 2.7%, ICC = 0.98) for research involving small samples (n = 20). In summary, low-repetition 5 RM strength testing offers greater utility as assessments of rowers, as they can be used to measure upper- and lower-body strength; however, only the leg press exercise is recommended for research involving small squads of elite rowers.